Genome wide analysis of rare copy number variations in alcohol abuse or dependence. (August 2018) - ,; Osorio, Jesús; Carrera, Indalecio; Páramo, María José; López, Nicolás; García, Ana; González, Ana María; Rodríguez, Juana María; Matalobos, Manuela; Pomares, Joaquín; Longo, María Jesús; Álvarez, Sandra; et al.
Abstract: Genetics plays an important role in alcohol abuse/dependence. Its heritability has been estimated as 45–65%. Rare copy number variations (CNVs) have been confirmed as relevant genetic factors in other neuropsychiatric disorders, such as autism spectrum disorders, schizophrenia, epilepsy, or Tourette syndrome. In the present study, we analyzed the role of rare CNVs affecting exons of coding genes in a sample from Northwest Spain genotyped using the Illumina Infinium PsychArray Beadchip. After rigorous genotyping quality control procedure, 712 patients with alcohol abuse or dependence and 804 controls were used for CNV detection. CNV calling was performed using PennCNV and cnvPartition, and analyses were restricted to CNVs of at least 100 kb and including at least 10 single nucleotide polymorphisms. Logistic regression was used to test for the effect of CNV as well as number of genes affected by CNVs on case/control status, after adjustment for demographic and experimental covariates. We have found an excess of deletions (p = 0.008) and genes affected by deletions (p = 0.017) in cases. This effect was restricted to the 14.8% of affected genes that are intolerant to loss-of-function mutations (gene count p = 0.009). The importance of this subset of genes is emerging in other psychiatric disorders of neurodevelopmental origin, suggesting that disturbance in neurodevelopment mediated by genetic alterations may be a risk factor for alcohol use disorder.